Social and Environmental Influences on Physical Activity Levels in Latina Adolescents. Issue 2 (7th July 2016) - Benes, Deborah; Dowling, Jacqueline; Crawford, Sybil; Hayman, Laura L.
Abstract: Objective: To examine social and environmental factors that affect moderate to vigorous physical activity (MVPA) in mid‐adolescent Hispanic females. Design and Sample: Secondary data analysis to examine social and environmental level factors related to MVPA levels in ( n  = 897) mid‐adolescent Hispanic females. Measures: Data were retrieved from the National Survey of Children's Health (2011/12). Logistic regression was used to estimate associations for factors with MVPA. Results: Significant mid‐adolescent predictors were English speaking, OR 1.64 (95% CI, 1.03–2.61); parental attendance of activities, OR 0.50 (95% CI, 0.31–0.81); peer support, OR 2.74 (95% CI, 1.75–4.29); supportive neighborhood, OR 1.52 (95% CI, 1.03–2.32); and safe school environment, OR 1.67 (95% CI, 1.01–2.74). Conclusion: Findings highlight the need for the development of age and culturally appropriate interventions to aid the improvement of participation levels in MVPA among the Latina adolescent population. Additionally, findings suggest recommendations for policy and future research.